Boosting the Performance of the Nickel Anode in the Oxygen Evolution Reaction by Simple Electrochemical Activation. (27th March 2017) - Shinagawa, Tatsuya; Ng, Marcus Tze‐Kiat; Takanabe, Kazuhiro
Abstract: The development of cost‐effective and active water‐splitting electrocatalysts that work at mild pH is an essential step towards the realization of sustainable energy and material circulation in our society. Its success requires a drastic improvement in the kinetics of the anodic half‐reaction of the oxygen evolution reaction (OER), which determines the overall system efficiency to a large extent. A simple electrochemical protocol has been developed to activate Ni electrodes, by which a stable NiOOH phase was formed, which could weakly bind to alkali‐metal cations. The electrochemically activated (ECA) Ni electrode reached a current of 10 mA at <1.40 V vs. the reversible hydrogen electrode (RHE) at practical operation temperatures (>75 °C) and a mild pH of ca. 10 with excellent stability (>24 h), greatly surpassing that of the state‐of‐the‐art NiFeOx electrodes under analogous conditions. Water electrolysis was demonstrated with ECA‐Ni and NiMo, which required an iR‐free overall voltage of only 1.44 V to reach 10 mA cmgeo −2 .